Development of healthier gummy candy by substituting glucose syrup with various fruit juice concentrates - Goztok, Serpil Pekdogan; Khiabani, Arezou Habibzadeh; Toker, Omer Said; Palabiyik, Ibrahim; Konar, Nevzat (WILEY, 2024)
The main objective of this study was to evaluate the effects of various formulations of fruit juice concentrates (pomegranate, grape, and sour cherry) on the pH, water activity, density, color, texture, and microstructure characteristics of candies instead of glucose syrup. The experimental points of the study were examined by a D-optimal mixture design to optimize the concentration of fruits used in the formulation and achieve excellent physicochemical characteristics. Fruit juice concentrates, either singly or in combination, were used as a complete substitute for glucose syrup in the formulation. Total fruit juice concentration used in the formulation was 54.07% and each of the fruit juice concentrations changed between 0 and 54.07% in the formulation. By combining these three fruit juices, 14 gummy candy samples were produced, depending on the Special cubic, cubic, and quadratic models that were used for the effects on the physicochemical properties (pH, water activity, density, L*, a*, b*, and chroma), and the texture profile analysis (TPA) (hardness, cohesiveness, springiness, and resilience) parameters according to independent variables. Results showed that pH, water activity, and density values of the gummy candy samples were found to be in the range of 2.22-3.08, 0.46-0.52, and 1.10-1.53 g/mL, respectively, and were significantly affected by different fruit juice concentrates (p < .05). The texture profile analysis showed that except for springiness, fruit juice concentrations significantly affected the texture profile (p < .05). The texture values, such as hardness, springiness, cohesiveness, gumminess, and resilience of the gummy candy samples, were determined as 146.1-938.8 N, 0.63-0.99, 0.75-1.19, 136.02-947.94 g, and 0.12-0.51, respectively. In addition, various fruit juice concentrates significantly affected the color parameters of gummy candies, and using pomegranate juice and sour cherry concentrates increased the +a* value of the gummy candies. Therefore, fruit juice-based gummy candies can be developed as value-added gummy candies by using fruit juice concentrates.
Keywords: confectionery; fruit juice concentrate; glucose syrup; healthy candy; natural sweeteners; SENSORY PROPERTIES; ULTRASOUND; SUCROSE; FOOD; Food Science & Technology